Endoscopic truncal vagotomy. Exploring the fourth space. A technical feasibility study in a porcine model - Kambiz Kadkhodayan, MD; Shayan Irani, MD (VideoGIE)
Background and Aims: Surgical truncal vagotomy is an effective treatment for refractory hyperacidity syndromes but is associated with significant perioperative risk, high cost, and morbidity. Endoscopic truncal vagotomy and EUS-guided vagal modulation may offer a minimally invasive alternative. In our porcine study, we evaluated the technical feasibility of endoscopic truncal vagotomy and EUS-guided targeting of the vagus nerves. Methods: A Yorkshire pig weighing 170 lbs was used for the study under an institutional review board–approved protocol. EUS was first used to identify both the anterior and posterior vagus nerves. The nerves were tattooed using a fine-needle aspiration needle. A mucosotomy, submucosal tunnel, and full-thickness myotomy were used to access the periesophageal adventitia. A tunnel was then created in the esophageal adventitia (fourth space), and the vagus nerve was identified and transected. After transection, the mucosotomy was closed using hemostatic clips. The procedure was repeated for the anterior and posterior vagus nerves. Postprocedure necropsy confirmed accurate EUS-guided tattoo placement, complete nerve transection, and we evaluated for intraprocedural adverse events. Results: The procedure was technically successful, with stable intraoperative vitals noted. On necropsy, both the anterior and posterior vagus nerves were accurately tattooed and completely transected in the lower esophagus. No evidence of leaks, mediastinal injury, or adverse events was observed. Conclusions: This study demonstrates technical feasibility of (1) EUS-guided vagus nerve identification and targeting using a fine-needle aspiration as needed, and (2) endoscopic transection of both the anterior and posterior vagus nerves. Controlled dissection, low carbon dioxide insufflation, and meticulous technique are essential for safety. Further research is needed to refine the technique, assess safety and efficacy, and explore its full clinical potential.